2008
DOI: 10.2190/iq.27.4.d
|View full text |Cite
|
Sign up to set email alerts
|

Family Systems and HIV/AIDS in South Africa

Abstract: This study examines the role of family in the care and support of people living with HIV/AIDS (PLWHA) as a way of reducing the burden of stigma in the family. The PEN-3 model provided the cultural framework for this study. Data were drawn from participants' responses in 27 focus groups interviews conducted in South Africa. Participants were asked to discuss experiences of people living with HIV and AIDS in the family. The results highlight the positive and supportive aspects of the family, acknowledge the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 30 publications
(43 reference statements)
4
93
0
Order By: Relevance
“…Since ill-health is often the responsibility of the collective, it was not uncommon for men living with HIV in our study to disclose to family members in an attempt to seek their support in coping and adapting to their seropositive status. Our findings support previous research, which highlights the significance of family systems with identifying ways to cope with one's HIV positive status (Iwelunmor et al, 2006). Some family members in turn were supportive following disclosure of seropositive status, and they provided home-based care for participants; whereas others felt ashamed and rejected participants.…”
Section: Discussionsupporting
confidence: 87%
“…Since ill-health is often the responsibility of the collective, it was not uncommon for men living with HIV in our study to disclose to family members in an attempt to seek their support in coping and adapting to their seropositive status. Our findings support previous research, which highlights the significance of family systems with identifying ways to cope with one's HIV positive status (Iwelunmor et al, 2006). Some family members in turn were supportive following disclosure of seropositive status, and they provided home-based care for participants; whereas others felt ashamed and rejected participants.…”
Section: Discussionsupporting
confidence: 87%
“…PEN-3 qualitative findings also provided indicators for designing a tailored recruitment protocol for a family-based genetic study on breast cancer (Ochs-Balcom, Rodriguez, and Erwin 2011). In a paper on family systems and HIV and AIDS, Iwelunmor et al (2006) reported that family systems can be sources of support, unique indigenous entities, and sources of stress when addressing the care and support needs of family members living with HIV and AIDS. However, the need to take into account families’ experiences with HIV and AIDS was critical in the development of interventions aimed at reducing the burden of HIV and AIDS-related stigma in the family and improve care and support for PLWHA (Iwelunmor et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Lear (1998) shows that some Roman Catholic churches in Kenya and Uganda have used words such as "Love faithfully to avoid AIDS" to discourage usage of condoms. Other recent studies (e.g., Iwelunmor et al, 2006;Campbell et al, 2007;Neville & Rubin, 2007) also reported both supportive and detrimental roles. The belief in faith healing and miracles was also found in our study, which means that many who know of their status may choose faith healing as a first choice of care, or combine it with care from a health institution.…”
Section: Discussionmentioning
confidence: 84%